Research on Data Modeling Platform Based on Big Data of Telecom - Leiming Shen; Zhiming Bie (Dianxin kexue)
The Hadoopdesigner system based on big data of telecom was designed.According to the characteristics of telecom data,the system adopted the data modeling platform which was designed based on the idea of metadata.It also combined with many ideas and theories of the data warehouse modeling.It provided a new method for the treatment of big data of telecom,also it provided the unified,standard,and visual model for different kinds of data,and greatly reduced the difficulty of meeting fleetly different requirments of services by a unified way,improved processing efficiency.